ANALISA WEBSITE MYDX MENGGUNAKAN METODE WEBQUAL 4.0 DI LINGKUNGAN DIVISI WHOLESALE SERVICE - Dika Wahyu Wibowo; Astriana Mulyani (Journal of Information System, Informatics and Computing, 2026)
The MyDX website is an internal system used by employees of the Wholesale Service Division to support payment administration and document management processes. In its implementation, several issues have been identified, particularly related to usability, clarity of information, and interaction quality, which may affect user satisfaction. This study aims to analyze the influence of website quality on user satisfaction using the WebQual 4.0 method, which consists of three dimensions: usability, information quality, and interaction quality. This research employed a quantitative approach by distributing questionnaires to 62 respondents selected using the Slovin formula. The data were analyzed using IBM SPSS through validity testing, reliability testing, and multiple linear regression analysis. The results indicate that partially, usability (Sig. 0.043 < 0.05) and interaction quality (Sig. < 0.001 < 0.05) have a significant effect on user satisfaction, while information quality (Sig. 0.244 > 0.05) does not have a significant effect. Simultaneously, the three website quality dimensions significantly influence user satisfaction.